Corruption and political risks in Latin American countries: a general view - Filipe, J. A. (2015)
In this paper, a general view over political risks and corruption is given. Latin america countries are studied in order to analyze the present situation about this topic on these countries. It is concluded that these countries historically have great potential to receive foreign investments and to make business and are potentially attractive to companies that consider to establish there. Anyway political risks are considerable and corruption is always present for these countries when investments are studies in the international scenario considering the business attractiveness. In the recent years corruption is perceived to be increasing.